CORRELATION OF SEVERAL FACTORS WITH STUNTING INCIDENCE IN CHILDREN UNDER FIVE - Nurzahwa, Syabna Hadni; Mardhiati, Retno; Novianus, Cornelis (Universitas Islam Negeri Alauddin Makassar, 2023)
Stunting is a problem in nutritional status that causes growth disturbances so that toddlers are shorter in age. This study aims to determine the relationship of several factors with events stunting in toddlers at the Kalibaru Health Center in Bekasi in 2022. This research is a quantitative research study with a design approach case control. The population in this study were toddlers stunting and not-stunting aged 12-59 months at the Kalibaru Health Center in Bekasi. The number of samples was 96 under fives which were determined using simple random sampling technique. This study uses primary data and secondary data. Data analysis used in this study was univariate analysis and bivariate analysis using Chi Square test. The results of univariate analysis were 19 (19.8%) low birth weight, 24 (25%) history of diarrheal disease, 14 (14.6%) history of acute respiratory infection, 42 (44.8%) breastfeeding were not exclusive, 18 (18.8%) were born prematurely and 33 (34.4%) were not given colostrum. The results of the bivariate analysis showed that there was a relationship between the incidence of stunting and birth weight, history of diarrheal disease, exclusive breastfeeding and premature birth (p value < 0,05). Researchers advise the health center to provide more information about stunting prevention.